Antibiotic prophylaxis of purulent and septical complications during surgical treatment of complicated gallstone disease on background of liver cirrhosis - S. D. Khimich; F. T. Muravyev (Сучасні медичні технології)
Purpose of the study. The goal of this investigation was to determine the main risk factors in development of purulent and septical complications during surgical treatment of complicated gallstone disease on background of liver cirrhosis.